Pre-Competition Anxiety and Self-Confidence of Wheelchair Basketball Players from China, Taiwan and Hong Kong. - Yang, Jinjin (2005)
Keywords: dept.hms; faculty_collection

Exercise modifications and strategies to enhance shoulder function - Ronai, P. (Strength and Conditioning Journal, 2005)
The purposes of this article are to identify exercise performance-related factors that may contribute to shoulder pain and dysfunction and to describe appropriate training strategies for promoting shoulder stability and enhanced function. This article is not intended to help the reader diagnose and treat injuries or prescribe therapeutic interventions. Strength and conditioning professionals should encourage injured clients to consult a physician, physical therapist, or other appropriate health care professional before starting a conditioning program. © National Strength and Conditioning Association.
Keywords: Exercise technique; Flexibility; Posture; Rotator cuff impingement; Scapular stability; Sensorimotor control; Strength; dept.hms